A typeface at a time. - Liu, Danielle Lik Wa. (2012)
The power of the image possesses a controlling influence over the subconscious mind of the viewer. Non-design literate communities / individuals fail to fathom the importance of a poster, or the significance of detail in an advertisement. A low regard is held for the creative community – as long as the message is legible, the rest is a secondary issue to be reckoned with. Not only does this cripple the potential capacity of visual media, it also undermines the power of graphic elements – in this case, typography. Educating the public on fundamental typefaces would perhaps reduce visual insensitivity, and instigate a legitimate respect for design.